Joint forest management in India / spread,performance and impact - Ravindranath,N.H. Sudha,P (Universities Press, 2008)
Contributed articles presented at the National Workshop on JFM at Crossroads: Future Strategy and Action Program for Institutionalizing Community Forestry in India 20-22 April, 2006, IIFM, Bhopal.